2010
DOI: 10.1002/jcp.22202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substrate stiffness and PDGF on the behavior of vascular smooth muscle cells: Implications for atherosclerosis

Abstract: Vascular disease, such as atherosclerosis, is accompanied by changes in the mechanical properties of the vessel wall. Although altered mechanics is thought to contribute to disease progression, the molecular mechanisms whereby vessel wall stiffening could promote vascular occlusive disease remain unclear. It is well known that platelet-derived growth factor (PDGF) is a major stimulus for the abnormal migration and proliferation of vascular smooth muscle cells (VSMCs) and contributes critically to vascular dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
75
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 53 publications
(69 reference statements)
7
75
0
Order By: Relevance
“…Our finding suggesting that local wall stiffness plays a role in the initiation of atherosclerosis lesions appears to be in agreement with other clinical (1,32), biological (2,10), and animal (42) studies. Interestingly, the animal study performed by Van Herck et al (42) showed that an increase of arterial stiffness promotes plaque development.…”
Section: Discussionsupporting
confidence: 93%
“…Our finding suggesting that local wall stiffness plays a role in the initiation of atherosclerosis lesions appears to be in agreement with other clinical (1,32), biological (2,10), and animal (42) studies. Interestingly, the animal study performed by Van Herck et al (42) showed that an increase of arterial stiffness promotes plaque development.…”
Section: Discussionsupporting
confidence: 93%
“…It is an important factor in inducing SMC proliferation and migration from arterial media to intima. Therefore, inhibiting the migration and proliferation of VSMC by suppressing the PDGF expression is also a new target for treatment of AS in recent years [20][21][22] . This study showed that puerarin inhibited the expression of PCNA and PDGF in rabbits in the pathological process of AS, decrease SMC proliferation, and significantly reduce the formation of plaque.…”
Section: Discussionmentioning
confidence: 99%
“…The degradation in the collagen stiffness is not as pronounced in the native specimens, whereby the collagen retains 60% of it mechanical stiffness in comparison to the unheated controls. Potentially this stiffness reduction may have negative implications if repopulation of smooth muscle cells occurs, as Brown et al (2010) demonstrated that a reduction to 61% of the native tissue's stiffness value caused vascular smooth muscle cells not to survive overnight in tissue culture on these reduced stiffness substrates. However, they also demonstrated that proliferation on an even stiffer substrate was far greater, a 4.5 fold increase in proliferation was observed in comparison to the native stiffness mimicking substrate.…”
Section: Discussionmentioning
confidence: 99%